Analysis of Hamster Tumor Cell Lines Isolated from Single Colonies Soon After Induction by Polyoma Strains Differing in Transplant Antigen Production - Hare, J. Donald (1967)
Tumor cell colonies, arising after the infection of hamster embryo cells with two strains of polyoma virus (PV) which differed in their capacity to induce the PV-specific transplant antigen, were isolated and studied for their transplant and tumor or “T” antigen content and growth characteristics in vitro and in vivo. Four of four tumor lines induced by the transplant immunogenic 3049 strain contained the transplant antigen, while only one of seven lines induced by the immunogenically deficient sp-D strain showed direct evidence for this antigen. T antigen was not detected by immunofluorescence in three tumor lines induced by the 3049 virus which contained the polyoma transplant antigen. No differences in growth capacity on plastic, in agar, or in the hamster subcutaneous tissue were apparent in spite of significant differences in transplant antigen content among the clones.